The Preoperative Neurological Evaluation. (October 2013) - Probasco, John; Sahin, Bogachan; Tran, Tung; Chung, Tae Hwan; Rosenthal, Liana Shapiro; Mari, Zoltan; Levy, Michael
Neurological diseases are prevalent in the general population, and the neurohospitalist has an important role to play in the preoperative planning for patients with and at risk for developing neurological disease. The neurohospitalist can provide patients and their families as well as anesthesiologists, surgeons, hospitalists, and other providers guidance in particular to the patient's neurological disease and those he or she is at risk for. Here we present considerations and guidance for the neurohospitalist providing preoperative consultation for the neurological patient with or at risk of disturbances of consciousness, cerebrovascular and carotid disease, epilepsy, neuromuscular disease, and Parkinson disease.